2019
DOI: 10.1177/1077558719858839
|View full text |Cite
|
Sign up to set email alerts
|

Misclassification of Medicaid Participation by Dual Eligibles: Evidence From the Medicare Current Beneficiary Survey

Abstract: Previous studies show that survey-based reports of Medicaid participation are measured with error, but no prior study has examined measurement error in an important segment of the Medicaid population—low-income adults enrolled in Medicare. Using the Medicare Current Beneficiary Survey, we examine whether respondent self-reports of Medicaid enrollment match administrative records and present several key findings. First, among low-income Medicare beneficiaries, the false negative rate is 11.5% when the self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The three pathways that we identify represent 70 percent of full Medicaid participants among older adults 65 and up (MedPAC and MacPAC, 2018). An additional limitation is that we define Medicaid coverage using self‐reports from ACS respondents, which are subject to misreporting (see, e.g., Boudreaux et al., 2015; Mellor, McInerney, & Sabik, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The three pathways that we identify represent 70 percent of full Medicaid participants among older adults 65 and up (MedPAC and MacPAC, 2018). An additional limitation is that we define Medicaid coverage using self‐reports from ACS respondents, which are subject to misreporting (see, e.g., Boudreaux et al., 2015; Mellor, McInerney, & Sabik, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Among low-income respondents, we found similar false negative and false positive rates (34% and 5%, respectively). In comparison, Mellor et al (2021) found a false-negative rate of 14.6% and a false-positive rate of 3.7% among low-income respondents aged 65 and older in the Medicare Current Beneficiary Survey (MCBS). Our study findings of notably higher and more accurate rates of Medicaid participation demonstrate an advantage of using the restricted-use HRS linked to MBSF data over the public use HRS survey data.…”
Section: Discussionmentioning
confidence: 99%
“…Our first contribution is methodological, in that we use the HRS data to compare rates of Medicaid participation defined from administrative data versus survey data. Previous research has shown substantial misreporting of Medicaid coverage among Medicare beneficiaries in the Medicare Current Beneficiary Survey (MCBS; Mellor et al, 2021). Because the HRS is frequently used to examine policy-relevant questions regarding older Americans’ health insurance coverage, it is important to quantify the extent to which Medicaid participation is misreported in the survey.…”
Section: Introductionmentioning
confidence: 99%